Effects of Mind-Mapping Teaching Strategy on Building Trade Students’ Academic Performance and Retention in Government Technical Colleges of Borno State, Nigeria - Ibrahim, Babagana; Tukur, Tafida (Journal of Research in Industrial Technology and Educational Studies, 2025)
The main purpose of this study was to investigate the effects of mind-mapping teaching strategy on Building Trade students’ academic performance and retention in government technical colleges of Borno state, Nigeria. Bricklaying, Blocklaying and Concreting (BBC) is a subject of Building Trade program that is designed to provide both knowledge and skill that enable learners to efficiently perform in all aspect of brick/block layer’s work and become self-reliant. Two research questions and two null hypotheses were set. The study employed quasi-experimental research design. The experiment was carried out on all 103 NTCII BBC students at Government Technical Colleges of Borno state. The study consisted of experimental group and control group each treated independently. The experiment lasted for a period of 6 weeks. The test instrument used was consisted of 40 multiple choice questions adopted from NABTEB past question papers and validated by experts form Department of Technology Education Modibbo Adama University, Yola.  Mean and standard deviation was used to answer Research questions, while ANCOVA was used to test the null hypotheses at 0.05 alpha levels and Bonferroni post-hoc test was used to find out where the significance lies. The finding of the study revealed that Mind-mapping teaching strategy improved more academic performance of Building Trade students than demonstration teaching method with Mean difference of 6.83% margin at Government Technical Colleges in Borno state, Nigeria. The Experimental Group (taught using Mind-mapping teaching strategy) students retain more academic performance than their counterparts in the control group (without treatment) by 9.62% margin at Government Technical Colleges in Borno State, Nigeria. Additionally, the research underscores that there was significant difference among the mean scores of Building Trade students taught using mind mapping teaching strategy and demonstration teaching method at government technical colleges of Borno State, Nigeria. There was significant difference among the mean scores of Building Trade students taught using mind-mapping teaching strategy and demonstration teaching method in their retention test at government technical colleges of Borno State, Nigeria. The study among others recommends that government and ministry of education should encourage the use of mind-mapping strategies in teaching building trade in Government Technical Colleges of Borno State, Nigeria.
Keywords: Mind Mapping Teaching Strategy; Academic Performance; Retention